D-dimer: The Risk Factor of Children's Severe Mycoplasma Pneumoniae Pneumonia - Qiu, Juan; Ge, Jin; Cao, Ling (Frontiers in Pediatrics, 2022)
Mycoplasma Pneumoniae (MP) is an important cause of community-acquired pneumonia in children, which can cause serious consequences. There has been some research into predicting Severe Mycoplasma Pneumoniae Pneumonia (SMPP) primarily focused on pre-treatment time by macrolide, pre-hospital course, CRP and LDH et.al. while seldom reporting on concoagulation status. We designed this retrospective study to compare the difference between SMPP and Non-severe MPP (NSMPP) with an attempt to find the risk factors, with a special focus on concoagulation status.